2022
DOI: 10.1177/03010066221108859
|View full text |Cite
|
Sign up to set email alerts
|

The inversion effect in word recognition: The effect of language familiarity and handwriting

Abstract: Humans have expertise with visual words and faces. One marker of this expertise is the inversion effect. This is attributed to experience with those objects being biased towards a canonical orientation, rather than some inherent property of object structure or perceptual anisotropy. To confirm the role of experience, we measured inversion effects in word matching for familiar and unfamiliar languages. Second, we examined whether there may be more demands on reading expertise with handwritten stimuli rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…When this is disrupted, the inversion effect is reported to occur [43]. Typically, holistic processing is associated with face recognition; regardless, Feizabadi reported that when participants were presented with handwritten letters rather than computer fonts, activity in the participants' right hemisphere was recorded [44], suggesting some holistic processing had been conducted. Strokes in the old-Japanese letter stimuli may have been used as indicators to unconsciously recognize and process Itaigana as handwritten letters rather than a computer font.…”
Section: Holistic Processing and Prediction Errormentioning
confidence: 99%
“…When this is disrupted, the inversion effect is reported to occur [43]. Typically, holistic processing is associated with face recognition; regardless, Feizabadi reported that when participants were presented with handwritten letters rather than computer fonts, activity in the participants' right hemisphere was recorded [44], suggesting some holistic processing had been conducted. Strokes in the old-Japanese letter stimuli may have been used as indicators to unconsciously recognize and process Itaigana as handwritten letters rather than a computer font.…”
Section: Holistic Processing and Prediction Errormentioning
confidence: 99%